Idleness as a form of resistance to Capitalism in Philip K. Dick’s Piper in the Woods - Raphael Yi Xian Thoo; Soon Seng Foong; Gheeta Chandran (Research Synergy Foundation Press, 2024)
In Philip K. Dick’s short story “Piper in the Woods”, an increasing number of personnel on Asteroid Y-3 began identifying themselves as plants rather than humans after an encounter with the natives. Because the plants were unconcerned with work, their superiors were alarmed and attempted to unravel the mystery behind such a drastic transformation. This research studies, via textual analysis from a Marxist perspective, the ways in which capitalist ideologies are portrayed, reproduced, and resisted in the story. It was found that generally, humans perceive productivity as an essential part of their nature, and the only way to become valuable is by working. Under capitalism, wage labour is indeed crucial both for the working class to earn a living and for capitalists to accumulate even more capital. By this logic, the plants and asteroid natives that are content with minimal labor were considered primitive savages, even though they are perfectly self-sufficient. This is perhaps ironic given mankind’s insights into the tremendous stress stemming from the need to always be productive and that becoming a plant could be a form of resistance. Nevertheless, the idleness of the former humans was treated simply as a mental disorder that has to be cured so that the status quo can be maintained. This study would hopefully prompt readers to examine stories such as this one from a more critical perspective and demand meaningful changes over simple solutions about issues arising from the capitalist system.